2011
DOI: 10.1137/100809167
|View full text |Cite
|
Sign up to set email alerts
|

Chasing Bulges or Rotations? A Metamorphosis of the QR-Algorithm

Abstract: The QR-algorithm is a renowned method for computing all eigenvalues of an arbitrary matrix. A preliminary unitary similarity transformation to Hessenberg form is indispensable for keeping the computational complexity of the subsequent QRsteps under control. When restraining computing time is the vital issue, we observe that the prominent role played by the Hessenberg matrix is sufficient but perhaps not necessary to fulfill this goal. In this paper, a whole new family of matrices, sharing the major qualities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 29 publications
1
32
1
Order By: Relevance
“…In [13] it was shown that every complex n × n matrix is unitarily similar to a matrix in condensed form (2.1). The position vector p can be chosen arbitrarily.…”
Section: Preliminariesmentioning
confidence: 99%
See 4 more Smart Citations
“…In [13] it was shown that every complex n × n matrix is unitarily similar to a matrix in condensed form (2.1). The position vector p can be chosen arbitrarily.…”
Section: Preliminariesmentioning
confidence: 99%
“…Rational Krylov spaces associated with a condensed form. It was shown in [13] that the unitary similarity transformation that maps a matrix to a given condensed form (2.1) is essentially uniquely determined. The argument depends on a connection with a certain sequence of rational Krylov subspaces associated with the condensed form.…”
Section: Examplesmentioning
confidence: 99%
See 3 more Smart Citations